COVID-19 lockdowns weigh heavily on youth: an analysis of the impact on BMI for Age Z scores in children and adolescents - Muna Abed Alah (14779534) (2024)
Background The COVID-19 pandemic has significantly impacted the lifestyle and health of children and adolescents. This study aimed to assess the lifestyle changes brought about by COVID-19-related school closures and their impact on the Body Mass Index for Age Z (BAZ) scores of governmental school students in Qatar. Methods An analytical cross-sectional study was conducted between June and August 2022 targeting students aged 8–15 years. Data on lifestyle behaviors were gathered through telephone interviews with parents of selected students. The BAZ scores before and after school closures that were automatically calculated by the electronic health records system were extracted. Results We completed 1546 interviews. We found a significant increase in unhealthy food categories, a reduction in physical activity and an increase in the screen time over the period of schools’ closure. The BAZ increased significantly by 0.30 (95% CI 0.26–0.35). The increase in BAZ scores was significantly higher among male students and the younger age group compared to females and older counterparts, respectively. The student’s age group, sex, nationality and change in physical activity were significant predictors of the change in BAZ scores. Conclusions School closures during the COVID-19 pandemic negatively impacted the lifestyle of students in Qatar and resulted in a significant increase in the BAZ scores. Other Information Published in: Journal of Public Health License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/pubmed/fdad287